2011
DOI: 10.1371/journal.pone.0023283
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Mining Polymorphic Microsatellite Markers In Silico

Abstract: An important emerging application of high-throughput 454 sequencing is the isolation of molecular markers such as microsatellites from genomic DNA. However, few studies have developed microsatellites from cDNA despite the added potential for targeting candidate genes. Moreover, to develop microsatellites usually requires the evaluation of numerous primer pairs for polymorphism in the focal species. This can be time-consuming and wasteful, particularly for taxa with low genetic diversity where the majority of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…Newbler performed well at assembling full-length cDNA contigs, and our results are in line with Mundry et al’s [64] findings that Newbler outperformed other assembly programs in simulated experiments. The N50 value reported here is comparable to de novo Newbler cDNA assemblies for other organisms: N50 = 1,735 bp in Oncopeltus fasciatus , Ewen-Campen et al [65]; N50 = 1,333 bp in Silene vulgaris , Sloan et al [51]; N50 = 1,588 bp in Spalax galili , Malik et al [66]; and N50 = 854 bp in Arctocephalus gazella , Hoffman & Nichols [67]. …”
Section: Discussionsupporting
confidence: 73%
“…Newbler performed well at assembling full-length cDNA contigs, and our results are in line with Mundry et al’s [64] findings that Newbler outperformed other assembly programs in simulated experiments. The N50 value reported here is comparable to de novo Newbler cDNA assemblies for other organisms: N50 = 1,735 bp in Oncopeltus fasciatus , Ewen-Campen et al [65]; N50 = 1,333 bp in Silene vulgaris , Sloan et al [51]; N50 = 1,588 bp in Spalax galili , Malik et al [66]; and N50 = 854 bp in Arctocephalus gazella , Hoffman & Nichols [67]. …”
Section: Discussionsupporting
confidence: 73%
“…In fact, recent studies have identified 26 polymorphic microsatellite by pyrosequencing in an endangered fish species of China [88] and 21 microsatellites loci from the threatened freshwater Yarra pygmy perch ( Nannoperca obscura ) [89]. However, few studies have been conducted to search for cDNA-associated microsatellites, like those identified in the Atlantic herring ( Clupea harengus ) [90], despite the potential for targeting candidate genes [91]. …”
Section: Resultsmentioning
confidence: 99%
“…In a subsequent pilot study, we showed that it was possible to obtain polymorphic microsatellites targeted towards candidate genes related to immunity and growth by selecting loci that appear variable in silico [30]. We also exploited homology to the dog ( Canis lupus familiaris ) genome to map transcripts to specific chromosomes, allowing the development of a genome-wide distributed panel of 104 validated, polymorphic SNPs [31].…”
Section: Introductionmentioning
confidence: 99%